Does Competence and Work Discipline Explanatory Factors For Educational Staff? - Kurniawan, Agung Widhi; Puspitaningtyas, Zarah (Economics and Business Journal (ECBIS), 2024)
Competence and work discipline are seen as important factors for improving the performance of educational staff in higher education. The purpose of this study was to determine the effect of work competence and discipline on the performance of educational staff at the Main Office of Makassar State University. Data collection using a questionnaire to 132 respondents. At the 0.05 significance level, the results of multiple linear regression analysis prove that competence and work discipline have an effect on the performance of educational staff. These results indicate that competence and work discipline are explanatory factors that can encourage educational staff to achieve the expected performance. The results of this study are expected to provide an understanding of human behavior in organizations, so that it can be useful for self-development and the ability of educational staff to achieve the expected performance.